Impact of the Internet on the Life of a Student (Triyuga Academic Journal, 2024)
The modernization and difficulty of Internet technology not only benefit users but also have unfavorable effects on users, particularly on students. It is based on the following objective: to find out the times of using of internet and Impact of internet use. According to a study of 125 students, Internet use has become addictive, more likely to have negative effects, and provide less support for academic activities. This research adopted a survey-based design for the collection of all the questionnaire used. The collected data were analyzed using Microsoft Excel 2007 statistical software. The research found a negative relationship between internet addiction and motivation to study. Those having internet addiction are found to be more depressed, stressed and anxious, as compared to those who are not having internet addiction. In a study conducted at private secondary school in Udayapur district of Triyuga Municipality, researchers found that those who rely on the internet, 45.6% respondents access time in internet during the meal time and 35% student use internet for more than 6 hour, 38% students frequently use internet for social media and 80% students internet to watch YouTube as well as 44% student use the internet for online games activity. Internet's impact on education is that students may spend more time on internet than on learning.